Proline production by transgenic plants of Swingle citrumelo and susceptibility to glufosinate ammonium - Carneiro, Cristine Elizabeth Alvarenga (2006)
The objective of this work was to evaluate the susceptibility to glufosinate ammonium of transgenic plants of Swingle citrumelo with high proline production. The mutant gene of the enzyme D1-pyrroline-5-carboxylate synthetase (P5CS), the rate-limiting enzyme in proline biosynthesis, was inserted into Swingle citrumelo plants. The expression of the gene p5cs caused up to 5-fold increase on the proline content in leaf tissues of transgenic plants treated with 200 mM glufosinate ammonium, when compared with control plants. Leaves of transgenic plants accumulated higher amounts of NH4+ than the nontransgenic control. The herbicide toxicity was evaluated using leaf disks cultivated in MS medium, containing different concentrations of glufosinate ammonium. The severity of the chlorosis, observed in leaf disks of transgenic plants, confirmed the higher susceptibility of Swingle citrumelo plants, with high proline production, to this herbicide.